1995
DOI: 10.1002/j.1460-2075.1995.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

The products of the SUP45 (eRF1) and SUP35 genes interact to mediate translation termination in Saccharomyces cerevisiae.

Abstract: The product of the yeast SUP45 gene (Sup45p) is highly homologous to the Xenopus eukaryote release factor 1 (eRF1), which has release factor activity in vitro. We show, using the two‐hybrid system, that in Saccharomyces cerevisiae Sup45p and the product of the SUP35 gene (Sup35p) interact in vivo. The ability of Sup45p C‐terminally tagged with (His)6 to specifically precipitate Sup35p from a cell lysate was used to confirm this interaction in vitro. Although overexpression of either the SUP45 or SUP35 genes al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
414
0
3

Year Published

1996
1996
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 457 publications
(429 citation statements)
references
References 56 publications
12
414
0
3
Order By: Relevance
“…The N-terminally truncated EF-1a-like polypeptides of eRF3, referred to as eRF3* (Ito et al+, 1998a), of S. pombe, S. cerevisiae, Xenopus laevis, and humans are known to bind to eRF1 both in vivo and in vitro (Stansfield et al+, 1995;Zhouravleva et al+, 1995;Ito et al+, 1998a)+ To further map the eRF1-binding site(s), S. pombe eRF3 was truncated by KpnI restriction enzyme at amino acid position 481, splitting into two fragments, eRF3⌬C and eRF3C (Fig+ 1)+ The ability of these polypeptides to interact with S. pombe eRF1 was examined by the GAL4-based two-hybrid system (Fields & Song, 1989;Chien et al+, 1991), as described previously (Ito et al+, 1998a)+ eRF1 and eRF3 polypeptides were cloned in-frame downstream of the GAL4 activation (ad) and binding (bd) domains, respectively, and the resulting plasmids were transformed in different pair-wise combinations into S. cerevisiae host strain HF7c (Feilotter et al+, 1994)+ (Note that the reciprocal fusions between release factors and ad/bd vectors were also tested in all two-hybrid analyses shown here, which gave essentially the same result+) The HF7c yeast strain contained a reporter gene, HIS3, under the control of GAL4-responsive elements, and an in vivo protein-protein interaction enabled the reporter transformant to grow on histidine-free minimal medium+ This two-hybrid assay indicated that the C-terminal segment eRF3C (amino acid positions 482-662) bound eRF1 (see Fig+ 4A, sample 1) similarly to eRF3* (positions 212-662), whereas the N-terminal segment eRF3⌬C (positions 1-481) and eRF3*⌬C (positions 212-481) did not (data not shown; see Fig+ 1)+ To confirm the interaction of truncated eRF3 polypeptides with eRF1 in vitro, the eRF3 segments were fused to their N-termini with glutathione S-transferase (GST), as described previously (Ito et al+, 1998a), and immobilized onto glutathione-agarose beads for the pull-down analysis+ S. pombe eRF1 was tagged at its N-terminus with a hexa-histidine sequence and purified by affinity to nickel-agarose beads (see Materials and Methods)+ The resin with bound GST-eRF3 polypeptides were incubated with purified His 6 -eRF1 and then washed to remove nonspecific proteins+ Bound proteins were eluted and analyzed by Western blotting to stain the eRF1-bearing histidine tag with an Ni-NTA-horseradish peroxidase conjugate+ When the eRF1 and eRF3 derivatives were mixed, immobilized eRF3, eRF3*, and eRF3C efficiently precipitated eRF1, as shown in the SDS-polyacrylamide gel analysis (PAGE) (Fig+ 2B, lanes 6, 8, and 10), whereas immobilized eRF3⌬C and eRF3*⌬C did not (Fig+ 2B, lanes 7 and 9)+ These results indicated that the eRF1-binding site on eRF3 resides in positions 482-662 and that the G domain is not involved in the binding+ It is known that S. pombe eRF3 and eRF3* are able to restore growth of the temperature-sensitive eRF3 strain, gst1-1 (Kikuchi et al+, 1988) by intergeneric complementation (Ito et al+, 1998a)+ Neither of the truncated polypeptides, eRF3C or eRF3⌬C, however, restored the viability of the gst1-1 strain (data not shown)+…”
Section: Binding Of Erf1 To the C-terminal Domain Of S Pombe Erf3mentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminally truncated EF-1a-like polypeptides of eRF3, referred to as eRF3* (Ito et al+, 1998a), of S. pombe, S. cerevisiae, Xenopus laevis, and humans are known to bind to eRF1 both in vivo and in vitro (Stansfield et al+, 1995;Zhouravleva et al+, 1995;Ito et al+, 1998a)+ To further map the eRF1-binding site(s), S. pombe eRF3 was truncated by KpnI restriction enzyme at amino acid position 481, splitting into two fragments, eRF3⌬C and eRF3C (Fig+ 1)+ The ability of these polypeptides to interact with S. pombe eRF1 was examined by the GAL4-based two-hybrid system (Fields & Song, 1989;Chien et al+, 1991), as described previously (Ito et al+, 1998a)+ eRF1 and eRF3 polypeptides were cloned in-frame downstream of the GAL4 activation (ad) and binding (bd) domains, respectively, and the resulting plasmids were transformed in different pair-wise combinations into S. cerevisiae host strain HF7c (Feilotter et al+, 1994)+ (Note that the reciprocal fusions between release factors and ad/bd vectors were also tested in all two-hybrid analyses shown here, which gave essentially the same result+) The HF7c yeast strain contained a reporter gene, HIS3, under the control of GAL4-responsive elements, and an in vivo protein-protein interaction enabled the reporter transformant to grow on histidine-free minimal medium+ This two-hybrid assay indicated that the C-terminal segment eRF3C (amino acid positions 482-662) bound eRF1 (see Fig+ 4A, sample 1) similarly to eRF3* (positions 212-662), whereas the N-terminal segment eRF3⌬C (positions 1-481) and eRF3*⌬C (positions 212-481) did not (data not shown; see Fig+ 1)+ To confirm the interaction of truncated eRF3 polypeptides with eRF1 in vitro, the eRF3 segments were fused to their N-termini with glutathione S-transferase (GST), as described previously (Ito et al+, 1998a), and immobilized onto glutathione-agarose beads for the pull-down analysis+ S. pombe eRF1 was tagged at its N-terminus with a hexa-histidine sequence and purified by affinity to nickel-agarose beads (see Materials and Methods)+ The resin with bound GST-eRF3 polypeptides were incubated with purified His 6 -eRF1 and then washed to remove nonspecific proteins+ Bound proteins were eluted and analyzed by Western blotting to stain the eRF1-bearing histidine tag with an Ni-NTA-horseradish peroxidase conjugate+ When the eRF1 and eRF3 derivatives were mixed, immobilized eRF3, eRF3*, and eRF3C efficiently precipitated eRF1, as shown in the SDS-polyacrylamide gel analysis (PAGE) (Fig+ 2B, lanes 6, 8, and 10), whereas immobilized eRF3⌬C and eRF3*⌬C did not (Fig+ 2B, lanes 7 and 9)+ These results indicated that the eRF1-binding site on eRF3 resides in positions 482-662 and that the G domain is not involved in the binding+ It is known that S. pombe eRF3 and eRF3* are able to restore growth of the temperature-sensitive eRF3 strain, gst1-1 (Kikuchi et al+, 1988) by intergeneric complementation (Ito et al+, 1998a)+ Neither of the truncated polypeptides, eRF3C or eRF3⌬C, however, restored the viability of the gst1-1 strain (data not shown)+…”
Section: Binding Of Erf1 To the C-terminal Domain Of S Pombe Erf3mentioning
confidence: 99%
“…The eRF3C domain that is sufficient for binding to eRF1 does not include the G-domain motifs+ This is in sharp contrast with other translational G proteins, elongation factors EF-Tu and EF-1a, or initiation factors IF2 and eIF-2, whose aminoacyl-tRNA or N-formylmethionyl-tRNA binding is controlled by G-domain function: GTP stimulates the association and GDP dissociates the complex+ There have been numerous reports that the N-terminal domain, including the G domain, of EF-Tu and EF-1a plays a crucial role in the binding of aminoacyl-tRNA directly or indirectly: the binding is diminished by mutations of Lys-4 (Laurberg et al+, 1998), Arg-7 (Mansilla et al+, 1997), Lys-9 (Laurberg et al+, 1998), Arg-58 , Lys-89 (Wiborg et al+, 1996), Asn-90 (Wiborg et al+, 1996), Gly-94 , His-118 (Jonak et al+, 1994), and Glu-259 (Pedersen et al+, 1998) of E. coli EF-Tu; Thr-62 of T. thermophilus EF-Tu (Ahmadian et al+, 1995); and Gly-280 of Salmonella typhimurium EF-Tu (Tubulekas & Hughes, 1993)+ Some of these substitutions, however, are known to affect the stability of the GTP form of EF-Tu/EF-1a relative to the GDP form, and thereby diminish the binding of aminoacyl-tRNA+ Because of the functional requirement for continuous delivery of aminoacyl-tRNA during protein elongation, the G-domain activity influences, directly or indirectly, the binding of aminoacyl-tRNA+ On the other hand, guanine nucleotides do not seem to influence the eRF1-eRF3 interaction+ They form a complex in vitro both in the presence (Zhouravleva et al+, 1995) or absence (Stansfield et al+, 1995;Frolova et al+, 1998) of GTP+ Therefore, the G-domain function of eRF3 may not be to change the binding of eRF1, but instead to change the binding of the ribosome or to catalyze final translocation of the ribosome+ Once eRF3 is associated with eRF1 before or after binding to the ribosome, the two probably remain associated via their C-termini interaction until their release from the ribosome, showing a clear functional difference between eRF3 and EF-Tu/EF-1a+ FIGURE 6. Comparison of the amino acid sequences of eRF3s and elongation factors EF-Tu and EF-1a+ The similarity alignments of eRF1s were accomplished using the PILEUP program from the GCG program package (Devereux et al+, 1984)+ Identical and similar amino acids are boxed in black and gray, respectively+ Asterisks indicate amino acids of T. aquaticus EF-Tu that are involved in tRNA binding in the three-dimensional structure (Nissen et al+, 1996)+ Daggers represent amino acids of S. pombe eRF3 that were mutated to alanine+ The number refers to the amino acid position counted from the N-terminal Met+ FIGURE 7.…”
Section: Uncoupling Between Erf1 Binding and G-domain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), should bind efficiently to eRF3, given that eRF3 mimics an EF-Tu function. Because eRF1 and eRF3 proteins from different eukaryotes are known to bind in vivo as well as in vitro (Stansfield et al 1995;Zhouravleva et al 1995), we thoroughly investigated the eRF3-binding site on eRF1 using the fission yeast, Schizosaccharomyces pombe, proteins. Consequently, two distinct sites were assigned, one to an internal region between amino acid positions 187-247, and the other to the Cterminal region as the primary and strongest binding site for eRF3 (Ito et al 1998a).…”
Section: Other Supports For Trna Mimicry In Eukaryotesmentioning
confidence: 99%
“…Second, S. cerevisiae eRF3 is encoded by an essential gene, while bacterial RF3 is encoded by a nonessential gene. Third, eRF3 and eRF1 bind in vivo and in vitro and exist as a heterodimer in S. cerevisiae cell lysates (Stansfield et al 1995;Zhouravleva et al 1995;Ito et al 1998a), while bacterial RF3 does not bind stably to RF1 or RF2 (Y. Kawazu, K.I. & Y.N., unpublished data; see Ito et al 1996).…”
Section: Translation Termination ᭧ Blackwell Science Limitedmentioning
confidence: 99%